Problems of Protection of Historical Industrial Buildings on the Example of the Port and Shipyard Complex in Gdynia - Hirsch, Robert; Łozowska, Celina (Protection of Cultural Heritage, 2021)
There are many historical buildings preserved in the port and shipyard areas of Gdynia, which are subject to specific changes due to changes in the functioning of the port and land use transformations. The most important of these buildings are under strict legal protection by being entered in the register of monuments. This ensures their preservation and often also their revalorization. Others, also valuable, but not under such strict protection - included only in historic monuments registers, are subject to adaptations and reconstructions, which cause the loss of some values, but allow at least partial preservation. Many buildings of this type have lost their functions, are abandoned and await re-development. Historic preservation in such situations is very problematic and requires the development of compromises. Transformation of historic buildings is inevitable. In order to determine the scope of protection and permissibility of interference, it is desirable to develop a method of assessing historic values, which would provide tools to objectivize the transformation processes.